Technological breakthroughs in modern wireless sensor applications - Sharif, Hamid R. 1958-; Kavian, Yousef S., 1978- (Advances in wireless technologies and telecommunication (AWTT) book series., 2015)
"This book brings together new ways to process and monitor data, and to put it to work in everything from intelligent transportation systems to healthcare to multimedia applications"--